The Use of Learning Media in Efforts to Increase Students' Learning Motivation in Aqidah Akhlak Subject at Mts Al-Azhar Medan - Prihartono, Syafira Anggraini; Harahap, Muhammad Yunan (Universitas Syiah Kuala, 2025)
This study aims to analyze the effectiveness of utilizing instructional media in enhancing students' learning motivation in Aqidah Akhlak subjects at MTs Al-Azhar Medan. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the use of instructional media, such as audio-visual media, teaching aids, and digital platforms, significantly enhances students' interest and active participation in the learning process. These media facilitate easier understanding of the material, make learning more engaging, and create an environment that fosters student involvement. In conclusion, the implementation of innovative instructional media plays a crucial role in increasing students' learning motivation, particularly in Aqidah Akhlak subjects. This study recommends that teachers continue to develop and creatively utilize instructional media to support more effective and enjoyable educational processes